1999
DOI: 10.1152/jn.1999.82.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies Against Cysteine String Proteins Inhibit Evoked Neurotransmitter Release at Xenopus Neuromuscular Junctions

Abstract: Cysteine string proteins (CSPs) are evolutionarily conserved proteins that are associated with synaptic vesicles and other regulated secretory organelles. To investigate the role of CSPs in vertebrate neuromuscular transmission, we introduced anti-CSP antibodies into the cell bodies of Xenopus spinal motor neurons that form synapses with embryonic muscle cells in culture. These antibodies produced a rapid (within 3-6 min), and in most cases complete, inhibition of stimulus-dependent neurotransmitter secretion.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
29
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 51 publications
4
29
0
Order By: Relevance
“…3) suggests that this pool of csp may also reach the plasma membrane via ongoing constitutive exocytosis. Several prior investigations have noted that perturbation of csp function in the regulated pathway does not affect spontaneous neurotransmitter release at nerve endings (16,44) or the basal secretory process in adrenal or pancreatic cells (22)(23)(24)47). These results support the hypothesis that csps evolved to perform a function important for the regulated secretory pathway.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…3) suggests that this pool of csp may also reach the plasma membrane via ongoing constitutive exocytosis. Several prior investigations have noted that perturbation of csp function in the regulated pathway does not affect spontaneous neurotransmitter release at nerve endings (16,44) or the basal secretory process in adrenal or pancreatic cells (22)(23)(24)47). These results support the hypothesis that csps evolved to perform a function important for the regulated secretory pathway.…”
Section: Discussionsupporting
confidence: 76%
“…The supernatant was mixed with 5ϫ concentrated Laemmli sample buffer and resolved on a SDS-polyacrylamide gel for immunoblot analysis as before (7,26,31). An antibody specific for the amino terminus of csp (N-end antibody) was obtained by covalently conjugating recombinant Xenopus csp 1-112 to Pierce's aminolink resin (following the manufacturer's instructions) and adsorbing csp antiserum (16) to this matrix, washing with phosphate-buffered saline, and eluting the bound antibody using 0.1 M glycine-HCl (pH 3.0). After adjusting the pH to 7.5 with 1 M Tris base, the antibody capable of binding the carboxyl terminus of csp was removed by passing the N-end antibody through an aminolink resin to which the recombinant carboxyl end of Xenopus csp (residues 137-197) was coupled.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In neurons, Csp is associated predominantly with synaptic vesicles (19), and in secretory cells it is found in large dense core or secretory granules (23,24). Studies of membrane dye labeling (25) and neurotransmitter release (26,27) indicated that Csp knockouts exhibit defective neurotransmitter exocytosis; presynaptic endocytosis and vesicle recycling appear to be intact. Studies in neuroendocrine (28) and endocrine cells (24) have confirmed that altered Csp expression elicits an impaired secretory phenotype.…”
mentioning
confidence: 99%
“…22) or a 1:1000 dilution of cortical granule lectin antiserum (a kind gift from Dr. J. Hedrick, University of California, Davis). The extract of Xenopus brain that served as a control in Fig.…”
mentioning
confidence: 99%